2017
DOI: 10.1016/j.resuscitation.2017.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular fibrillation waveform characteristics of the surface ECG: Impact of the left ventricular diameter and mass

Abstract: Frequency characteristics of VF were consistently lower in case of an increased LV diameter. Whereas LV mass does not affect the frequency of the VF waveform, amplitudes seem higher with increasing mass. These findings add to the current knowledge of factors that modulate VF characteristics of the surface ECG and provide insight into factors which may be accounted for in future studies on VF-guided resuscitative interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…There have been a few studies that attempted to infer the underlying characteristics of the heart based on features extracted from the electrograms. The analysis of the electrogram characteristics (particularly frequency) were observed to have a correlation with the diameter of the left ventricle [20], but there was no observed relation to the mass of the heart. The conduction velocity and amplitude were used as determining factors for reducing the recurrence of future VT episodes [21].…”
Section: Current Researchmentioning
confidence: 89%
See 1 more Smart Citation
“…There have been a few studies that attempted to infer the underlying characteristics of the heart based on features extracted from the electrograms. The analysis of the electrogram characteristics (particularly frequency) were observed to have a correlation with the diameter of the left ventricle [20], but there was no observed relation to the mass of the heart. The conduction velocity and amplitude were used as determining factors for reducing the recurrence of future VT episodes [21].…”
Section: Current Researchmentioning
confidence: 89%
“…However, the lethal nature of VA and the practical infeasibility in obtaining APP characteristics in a non-invasive manner are obstacles in studying VA. Given that literature has shown that there exists relationships between the electrograms and APP characteristics (and in turn could influence specific events) [20,22], this dissertation will develop adaptive signal decomposition methods to extract information from multi-channel electrograms that could be used to infer specific events and the APP characteristics during VAs.…”
Section: Motivationmentioning
confidence: 99%
“…AMSA is directly related to the heart metabolic status, correlating with myocardial energy phosphates concentrations. However, little is known about other patient characteristics that may influence the ventricular fibrillation waveform [4,51]. For example, the presence of comorbidities is a well known risk factor for poor survival.…”
Section: Amplitude Spectrum Area In Retrospective Clinical Studiesmentioning
confidence: 99%
“…The principal ECG changes in patients with increased LV-D and LV-S in LV hypertrophy include augmented QRS amplitude, prolonged QRS conduction time, changes in instantaneous and mean QRS vectors, ST depression and/or T-wave inversion, and P-wave abnormalities, such as left atrial enlargement ( 7 , 8 ). VF frequency was consistently lower in patients with an increased LV diameter ( 9 ). However, these ECG changes were neither sensitive nor specific for increased LV-D or LV-S detection.…”
Section: Introductionmentioning
confidence: 99%